2020
DOI: 10.3390/ijerph17228632
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Land-Use Change Scenarios for Ecosystem Services and their Trade-Offs in the Ecological Conservation Area in Beijing, China

Abstract: It is generally believed that land-use changes can affect a variety of ecosystem services (ES), but the relationships involved remain unclear due to a lack of systematic knowledge and gaps in data. In order to make rational decisions for land-use planning that is grounded in a systematic understanding of trade-offs between different land-use strategies, it is very important to understand the response mechanisms of various ecosystem services to changes in land-use. Therefore, the objective of our study is to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…The accuracy of the model in simulating the land‐use situation of the XMA was verified by the Figure of Merit (FoM)() index. The FoM index of the FLUS model for simulating the land‐use pattern was 0.67, which proved that the FLUS model was more applicable and could simulate the future land use of the XMA better (Chen et al, 2017; Li et al, 2020). The spatial supply maps of CR, CS, and R were produced by the IUEMS model (see details in Equations () to () in Section 2.5).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The accuracy of the model in simulating the land‐use situation of the XMA was verified by the Figure of Merit (FoM)() index. The FoM index of the FLUS model for simulating the land‐use pattern was 0.67, which proved that the FLUS model was more applicable and could simulate the future land use of the XMA better (Chen et al, 2017; Li et al, 2020). The spatial supply maps of CR, CS, and R were produced by the IUEMS model (see details in Equations () to () in Section 2.5).…”
Section: Methodsmentioning
confidence: 96%
“…ESs are not completely independent but interact with each other in a complex nonlinear relationship, of which the more typical ones are the trade‐off and synergy relationships (Li et al, 2020). The Pearson correlation coefficient r is used to characterize the trade‐off and synergy relationship between ESs in this paper, and the formula is as follows: r=i=1nxixtrue¯yiytrue¯i=1n()xigoodbreak−truex¯2i=1n()yigoodbreak−truey¯2 where r is the correlation coefficient; i is the order of years, from 1 to n; n is the total number of years; xi is one ES at a time i; and yi is another ES at time i.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the area of positive synergy between the former three pairs was increasing. Some studies concluded for other regions that grain supply and HQ are trade-offs (Li Z et al, 2020;Zhang et al, 2020). In this study, FS includes both grain and meat production.…”
Section: How Did the Ess Affect Each Other?mentioning
confidence: 96%
“…In this study, FS includes both grain and meat production. Grain production by cropland reduced HQ, so FS and HQ are trade-offs in cropland areas (Li Z et al, 2020). But for the meat production by grassland, its increase was mainly caused by forage production increases, resulting from the ecological construction on sandy land and desert.…”
Section: How Did the Ess Affect Each Other?mentioning
confidence: 99%